RHETORICAL MOVE AND GENRE KNOWLEDGE DEVELOPMENT ANALYSIS OF THESIS AND DISSERTATION ABSTRACTS OF LOCAL AND INTERNATIONAL GRADUATE LECTURERS - Tara Devina Putri, - (2021)
In recent years, there has been surge of interest in the study of research abstracts and its rhetorical structure. While the number of studies in rhetorical moves of RA abstracts keeps growing, thesis and dissertation abstracts still receive little attention, especially in regard to the relationship between genre knowledge and its rhetorical realization. The current study seeks to identify the variations of rhetorical move manifestation in abstracts of master's theses and dissertations written by local and international graduate lecturers as well as to explore the relationship between the manifestations and the author's genre knowledge development. This study adopted a qualitative approach with Hyland's (2000) five-move analysis model as the primary framework of the study. The findings revealed that there were similarities in the realization of rhetorical structure of abstracts by the local and international graduates. The study also discovered that the author's educational level and supportive academic environment contribute to their genre knowledge development. The results of this study provide a clearer picture to aid in the development of a universal guideline for abstract writing in final papers for higher education.